Optimization of hydrocyclon for phosphatic rock separation using CFD - Felipe Orlando da Costa; Felipe Leonardo Barcelos Mateus; Irineu Petri Júnior (The Journal of Engineering and Exact Sciences)
Hydrocyclones are equipment for the separation of solid-liquid and liquid-liquid mixtures through the centrifugal flow. The phosphate rock is an essential raw material to the industry of phosphate fertilizers. The mineral needs to be concentrated in its processing, and this can be done through hydrocyclones, considering its robustness and low operation costs. This work aimed to use the computational fluid dynamics to study different multiphase models to represent the hydrocyclones, as well as modifications to its geometry to increase its efficiency. Three multiphase models were studied in order to analyze their efficiency in simulating the separation through hydrocyclones: Eulerian-Lagrangian, Eulerian-Eulerian, and Mixture Model. In order to optimize the separation process and reduce operating costs, 11 modifications were proposed in the geometry of HC11, called B1, B2, B3, C1, C2, C3, D1, D2, E1, E2 and E3. The first 8 proposals involved changes in the vortex finder and the last 3 proposals added a wall in the air core formation region. Geometry and mesh were generated in the GAMBIT® software and the simulation was made in the FLUENT® 19.2 software. In order to compare the multiphase models, the individual and overall efficiency were used along with the experimental results. The Mixture model had the smallest relative error and was used for the subsequent simulations. The parameters evaluated to measure the optimization of HC11 were the pressure drop (?P), the liquid ratio (RL) and the overall efficiency (?). The results obtained for each of the proposals were compared with the value found in the HC11 simulations to evaluate the possible optimization. With that, it was possible to verify that modifications B2, B3, and D1 improved all the parameters evaluated, optimizing the separation process and reducing energy costs involved in the operation.